Arginine metabolism in Trichomonas vaginalis infected with Mycoplasma hominis - Morada, Mary; Manzur, Mafruha; Lam, Brian; Tan, Cho; Tachezy, Jan; Rappelli, Paola; Dessì, Daniele; Fiori, Pier L; Yarlett, Nigel (Microbiology (Reading, England), 2010)
Both Mycoplasma hominis and Trichomonas vaginalis utilize arginine as an energy source via the arginine dihydrolase (ADH) pathway. It has been previously demonstrated that M. hominis forms a stable intracellular relationship with T. vaginalis; hence, in this study we examined the interaction of two localized ADH pathways by comparing T. vaginalis strain SS22 with the laboratory-generated T. vaginalis strain SS22-MOZ2 infected with M. hominis MOZ2. The presence of M. hominis resulted in an approximately 16-fold increase in intracellular ornithine and a threefold increase in putrescine, compared with control T. vaginalis cultures. No change in the activity of enzymes of the ADH pathway could be demonstrated in SS22-MOZ2 compared with the parent SS22, and the increased production of ornithine could be attributed to the presence of M. hominis. Using metabolic flow analysis it was determined that the elasticity of enzymes of the ADH pathway in SS22-MOZ2 was unchanged compared with the parent SS22; however, the elasticity of ornithine decarboxylase (ODC) in SS22 was small, and it was doubled in SS22-MOZ2 cells. The potential benefit of this relationship to both T. vaginalis and M. hominis is discussed.
Keywords: Arginine; hydrolasy; Hydrolases; Mycoplasma hominis; ornithindekarboxylasa; arginin; sekvenční seřazení; Ornithine Decarboxylase; Trichomonas vaginalis; Amino Acid Sequence; Sequence Alignment; Protozoan Proteins; Molecular Sequence Data; protozoální proteiny; molekulární sekvence - údaje; sekvence aminokyselin